Concept of Parental Treatment in Surah Luqman Verses 13-19: An Analysis of Tafsir Al-Misbah and Tafsir Fi Zilal Al-Qur'an - Adlan Fauzi Lubis; Okta Rosfiani; Husnul Hanifah Kamawi Putri; Cahya Lestari Agustin; Ilham Asyam Fajariyanto Wisnu; Muhammad Farhan (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This article investigates parenting patterns within the Al-Quran, specifically focusing on verses concerning parent-child communication. Examining the education and guidance provided by four parents, the study highlights the risks associated with parenting approaches diverging from Quranic values, potentially leading to children's mental health issues. Notably, authoritarian parenting is explored for its negative impact on children's lives and disobedience towards elders. Drawing insights from Surah Luqman [31]:13-19, the research reveals a balanced blend of authoritarian and democratic parenting rooted in Quranic principles, emphasizing rational control. Addressing child depression, the study advocates strategies such as prohibiting shirk, fostering compassion, attending to actions, prayer, patience, and discouraging arrogant attitudes. This research contributes valuable perspectives on effective, Quranic-aligned parenting strategies, offering insights into mitigating mental health challenges and disobedience among children.